2019
DOI: 10.1002/adfm.201901061
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stretchable and Wearable Thermotherapy Pad with Micropatterned Thermochromic Display Based on Ag Nanowire–Single‐Walled Carbon Nanotube Composite

Abstract: Due to the increasing interest in wearable devices, flexible and stretchable film heaters have been widely studied, as alternatives to heaters with conventional rigid shapes. Herein, a highly stretchable film heater (SFH) based on the silver nanowire (Ag NW)-single-walled carbon nanotube composite with a thermochromic display on a polydimethylsiloxane (PDMS) substrate is successfully fabricated. The SFH shows excellent electrical conductivity, high mechanical stretchability, and outstanding reliability, with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 52 publications
1
70
0
Order By: Relevance
“…The most common types of thermotherapy pads are based on a heating component and a far-infrared paste or gel 11 . The conventional thermotherapy pads have many drawbacks that limit their usage in wearable devices 11,14,15 . The first drawback is the lack of transparency, which is necessary to see the treatment effect without the need for removing the pads.…”
Section: Introductionmentioning
confidence: 99%
“…The most common types of thermotherapy pads are based on a heating component and a far-infrared paste or gel 11 . The conventional thermotherapy pads have many drawbacks that limit their usage in wearable devices 11,14,15 . The first drawback is the lack of transparency, which is necessary to see the treatment effect without the need for removing the pads.…”
Section: Introductionmentioning
confidence: 99%
“…It is highly significant that the device does cloak the human body actively with high wearability and switchability between the visible and IR spectrum bands as a complete working wearable device because most of the previously reported devices so far only suggested the fundamental concepts that merely examine prospective potential. [10,15,24,25]…”
Section: Active Imperceptible Artificial Skin On the Multispectral Rementioning
confidence: 99%
“…Inspired by the active and autonomous cloaking system from nature, recent technological advances offered a number of physical mechanisms to reconstruct the cloaking functionalities of cephalopods. Much of previous literature concentrated on altering colors within the visible wavelength using various methods such as electrochromic, thermochromic, and mechanochromic phenomena, [4][5][6][7][8][9][10][11] while several researches also delved into the cloaking techniques in the IR regime utilizing the metamaterials, [12][13][14] electro-actuation for IR reflection [15] or simply by adjusting device temperature to match background temperature [16] since the temperature (or radiated heat) can be directly translated into the IR signals. However, most of them realized either visible or IR imperceptible systems only; not dual modes in a single device structure that can readily switch between the visible and IR mode depending on a desirable situation.…”
mentioning
confidence: 99%
“…The flexible heaters that were fabricated exhibited fast and accurate response at various voltages. Kim et al reported stretchable film heaters using a spray‐coated AgNW/SWCNT hybrid composites that exhibit electrical and thermal stability without deterioration after 10 000 stretching cycles. The stretchable heater can be heated up to the target temperature (60°C) accurately even during a stretching state with the tensile strain of 50% (Figure H).…”
Section: Hybrid Nanomaterialsmentioning
confidence: 99%